Le courage et les mots de la peur dans le Lachès et le Protagoras - Lévystone, David (Classical Association of Canada, 2006)
The amount of attention that Plato gives to the virtue of courage can be interpreted as a symptom of the difficulties he faced in integrating it into his virtue science theory. His answers are never exactly the same, even in two dialogues of youth, the Laches and Protagoras, which are supposed to give a more accurate picture of the teaching of Socrates himself. Through an analysis of the terminology of fear in these two texts, it becomes clear that Plato, in distinguishing phobos from deos, implicitly agrees with the impossibility of simply reducing courage to science. This perspective is likely to modify our comprehension of the intellectualist theory of Socrates himself, at least with regard to courage. ©The author ©Classical Association of Canada
The courage and the words of the scare in Laches and Protagoras
Keywords: Protagoras; Courage; Mots